Plasmids and pheromone response of the beta-lactamase producer Streptococcus (Enterococcus) faecalis HH22. - Murray, B E (1988)
Streptococcus (Enterococcus) faecalis HH22 is a clinical isolate that produces beta-lactamase and is resistant to various other antimicrobial agents. In this study, HH22 was found to contain three conjugative plasmids and a conjugative transposon. pBEM10 encodes beta-lactamase, gentamicin resistance, and a response to the peptide pheromone cAD1; pAM323 encodes erythromycin resistance; and pAM324 encodes no known resistance. The latter two plasmids respond to pheromones designated cAM323 and cAM324 which are unrelated to other previously characterized pheromones. pBEM10 and pAM323 are the second and third examples of naturally occurring R plasmids that confer a sex pheromone response.